2007
DOI: 10.1007/s10096-007-0292-6
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus infection of implantable cardioverter-defibrillators and pacemakers: case report and literature review

Abstract: Presented here is a case of implantable-cardioverter-defibrillator infection caused by Aspergillus flavus and a review of 14 previously reported Aspergillus infections of pacemakers or implantable cardioverter-defibrillators. Among all 15 cases, fever was the most common presenting feature (11 patients). Three patients presented with generator-pocket inflammation. Transthoracic echocardiography was performed on eight of 13 patients with endocarditis, revealing vegetations in only one. Transesophageal echocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Nearly all articles included small numbers of patients that satisfied the inclusion criteria, ranging from one to eight patients. We identified 48 cases from 41 individual studies that satisfied the prespecified inclusion criteria 9–49 . Among these patients, the mean age was 58 years, and 31% were female.…”
Section: Resultsmentioning
confidence: 99%
“…Nearly all articles included small numbers of patients that satisfied the inclusion criteria, ranging from one to eight patients. We identified 48 cases from 41 individual studies that satisfied the prespecified inclusion criteria 9–49 . Among these patients, the mean age was 58 years, and 31% were female.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these cases have been seen with lead infections and endocarditis often with tricuspid valve vegetations [ 4 ]. An article published in 2007 [ 6 ] reviewed 15 cases of Aspergillus associated pacemaker and ICD infections, of which only two had pocket infections. So far only four cases have been reported in association with pacemaker pocket infection and all of these occurred either acutely or sub-acutely.…”
Section: Discussionmentioning
confidence: 99%
“…Like Pincus et al, their cases also had risk factors like diabetes, but eventually did well with surgical and medical treatment. Cobo et al [ 6 ] reported a 74-year-old woman presenting with pocket infection, which was later found to be from Aspergillus favus . An Echocardiogram in addition showed vegetations in the cardiac leads.…”
Section: Discussionmentioning
confidence: 99%